ANALISIS SENTIMEN PENGGUNA LAYANAN TRANSPORTASI ONLINE GOJEK DAN INDRIVER DENGAN ALGORITMA SUPPORT VECTOR MACHINE - Siburian, Yosepha; Cristian, Yusticio; Puri, Anin Dita Sekar; Manurung, Onesimus Gust; Tamba, Saut Parsaoran (Politeknik Bisnis Indonesia, 2025)
Online transportation is a service that utilizes digital technology, such as mobile applications, to make it easier for users to book trips with just a touch on the phone screen. This convenience makes online transportation increasingly popular, especially in big cities in Indonesia. Two online transportation services that are widely used in Indonesia are Gojek and InDrive. These two platforms are inseparable from user opinions, which greatly affect the desires and competitiveness of each service. This study aims to conduct sentiment analysis on user reviews from the Google Play Store in order to compare the two applications using the Support Vector Machine (SVM) algorithm. This study shows that most of the 1000 Gojek and InDrive user reviews on the Play Store contain negative sentiment, especially related to driver delays and application disruptions. The Support Vector Machine (SVM) algorithm provides the highest accuracy of 86.11% at a training and test data ratio of 80:20, and shows relatively stable performance at other ratios. The dominant words in positive reviews are